PENINGKATAN KETERAMPILAN MELALUI PELATIHAN BOLU NANGKA SEBAGAI IDE BISNIS DI KELURAHAN KLAWUYUK - Susetyowati Sofia; Agilistya Rahayu; Syahrul Muarif; Nirmala Husnun Nur Afifah; Nuraini Fitra Salsabila; Rainhard Raimond Segidifat; Dia Fitrianingsih Malik (P3M Politeknik Negeri Malang, 2025)
There are great business opportunities in Sorong City, especially in the development of souvenir products that are still minimal. One of the proposed innovations is making sponge cake with jackfruit as the main ingredient, which has not been widely explored in Sorong City. The training aimed at mothers at the Al-Kausar Ta'lim Assembly aims to provide a basis for entrepreneurship and motivate them to create new innovations that can open up new business opportunities and jobs. Through this training, it is hoped that participants can develop skills in making jackfruit cake and take the first step towards economic independence as entrepreneurs. Jackfruit cake training is considered an important business idea to improve entrepreneurship and member skills to support community empowerment at the Al-Kautsar Tak'lim Assembly. This training is held with the aim of showing the potential of the jackfruit cake business as a growing economic opportunity. Through a series of training sessions, participants are invited to understand the related financial aspects, business management, marketing strategies, and jackfruit cake making techniques. This training emphasizes the development of creativity and entrepreneurial spirit. In addition, this training also builds strong community ties and increases the resilience of related parties. With the spirit of togetherness and knowledge gained, it is expected that participants can apply new skills to develop a jackfruit cake business independently. The success of this training creates a positive foundation for local economic growth and strengthens social unity in the Al-Kautsar Tak'lim Assembly.